A Series of Potent CREBBP Bromodomain Ligands Reveals an Induced‐Fit Pocket Stabilized by a Cation–π Interaction1. Issue 24 (12th May 2014) - Rooney, Timothy P. C.; Filippakopoulos, Panagis; Fedorov, Oleg; Picaud, Sarah; Cortopassi, Wilian A.; Hay, Duncan A.; Martin, Sarah; Tumber, Anthony; Rogers, Catherine M.; Philpott, Martin; Wang, Minghua; Thompson, Amber L.; et al.
Abstract The benzoxazinone and dihydroquinoxalinone fragments were employed as novel acetyl lysine mimics in the development of CREBBP bromodomain ligands. While the benzoxazinone series showed low affinity for the CREBBP bromodomain, expansion of the dihydroquinoxalinone series resulted in the first potent inhibitors of a bromodomain outside the BET family. Structural and computational studies reveal that an internal hydrogen bond stabilizes the protein‐bound conformation of the dihydroquinoxalinone series. The side chain of this series binds in an induced‐fit pocket forming a cation–π interaction with R1173 of CREBBP. The most potent compound inhibits binding of CREBBP to chromatin in U2OS cells.